Lymphatic Leakage after Surgery for Neuroblastoma: A Rare Complication? - Froeba-Pohl, Alexandra; Muehling, Jakob; Vill, Katharina; Grote, Veit; Komm, Tim; Seitz, Dorothee; Kappler, Roland; von Schweinitz, Dietrich (European Journal of Pediatric Surgery, 2020)
Introduction Neuroblastoma is the most common extracranial solid tumor in infancy. It is responsible for around 15% of all oncological deaths during childhood. Due to its retroperitoneal location, neuroblastoma is invasively growing directly in and around the lymphatic duct. Consecutively, lymphatic leakage (LL) after surgery for neuroblastoma is a known complication. The purpose of this study is the investigation of frequency and impact of this complication.Material and Methods Between February 2003 and December 2016, 204 patients with neuroblastoma received surgical treatment in our department. A retrospective analysis for macroscopical extent of resection, duration of drainage postsurgery, maximum amount of fluid drained in 24 hours, MYCN amplification status, therapeutic options for LL, follow-up status, and overall survival was performed.Results A total of 40% of patients (82/204) showed LL to some extent. In patients with MYCN amplification, LL was seen significantly more often than in patients without MYCN amplification status (p = 0.019). LL was also significantly correlated with extent of surgery (p = 0.005). Follow-up status and overall survival were significantly inversely associated with LL (p = 0.004 and p = 0.0001). LL was self-limiting in all cases. There was a trend toward shorter duration of LL if either no special therapy was chosen or total parenteral nutrition (TPN) was administered (p = 0.0603).Conclusion We show that LL in neuroblastoma is a common complication of tumor resection and occurring more often than anticipated. Since, in our study cohort, all cases of LL were self-limiting, we question the indication for invasive therapy besides supporting measures.
Keywords: neuroblastoma; lymphatic leakage; chylous ascites; outcome